PLURICENTRISM IN THE GERMAN STANDARD LANGUAGE AND THE GERMAN LANGUAGE FOR SPECIAL PURPOSES - KUBACKI, Artur Dariusz (Comparative Legilinguistics, 2014)
In this article, the author analyses pluricentrism/polycentrism in the German standard language and the German LSP. Until the eighties of the 20th century, the German language was treated as a monocentric language and the variant used in Germany was perceived as the model and normative variant. This had a direct impact on the method of teaching German as a foreign language (also in Poland). In the process of teaching, teachers referred only to social, political and economic situation in Germany. Even during German language university courses the variants of the German language used in other German-speaking countries, such as Austria, Switzerland, Luxembourg and Liechtenstein, were rarely discussed and the German language used in Eastern Belgium and Southern Tyrol in Italy was never mentioned. The differences between the variants of the German language can be seen at every level of the language: phonetic, morphological, syntactic, lexical and even pragmatic one. What is interesting, they can be found not only in the standard language (Gesamtsprache), but also in LSP (Fachsprache). In the article, the author shows these differences with regard to both the standard language and LSP. Moreover, he analyses their consequences for German language teaching and the process of translation.